HYDRODYNAMIC MODEL OF UNSTEADY MOTOR HIGH-FLOW - , А. В. (Municipal economy of cities (Technical science), 2013)
It is proposed simulation model of the hyperbolic type of unilateral high-intensity stationary traffic on the main highway from Lumped inflows and outflows of the minor side roads. Application of the Laplace transform method for the approximate solution of an expansion in the small parameter corresponding boundary value problem.